Basic concepts and models of educational policy analysis - Melia Putri Utami; Rts Rista Maharani; Yelvi Apriandini; Alief Firmansyah (Universitas Muhammadiyah Enrekang, 2024)
Education is a crucial topic to discuss because typically, human intelligence is judged by how much education one has attained. Policy analysis is an applied social research systematically arranged to understand the substance of policies to clearly grasp information regarding the issues addressed by the policy and the potential issues that may arise as a result of policy implementation. Understanding policy models is essential to ensure that the resulting policies can lead to the success of educational objectives. This research method employs a qualitative approach. The research model utilizes library research, with inductive-deductive analysis derived from several literature analyses (O'Dwyer & Bernauer, 2013; Moser & Korstjens, 2018). The aim of educational policy analysis is to analyze educational data and information and to maintain aspects within the process of designing and making a policy. It has 6 characteristics of education and there are 3 types of Education Policy Formulation Models.